SELF-BUILD FLUORINATED STRUCTURANTS FOR SURFACE TREATMENT - Castaner, L (International Scientific and Current Research Conferences, 2021)
Another class of alkyl-and perfluoroalkyl-containing urea and amide subordinates was integrated from amino corrosive subsidiaries. The greater part of these mixtures showed superb gelation conduct in natural solvents at low focuses. A couple structures chose from the underlying screening were utilized for surface alteration of sinewy substrates to make hydrophobic and oleophobic composites. The hydrophobic and oleophobic practices of these composites were credited to a mix of expanded surface unpleasantness and the alkyl/fluorinated functionalities present in the spine.